The rough guide to the best country blues you've never heard. Vol. 2 [compact disc]. - Brown, Henry, 1906-1981; Bradley, Tommie; Bull City Red; Moore, Kid Prince; Davenport, Jed; Vinson, Walter, 1901-1975; Reed, Long Cleve; Hull, Papa Harvey; Wallace, Minnie; Childers, Virgil; McClintock, Lil; Campbell, Gene (Vocalist); et al. (World Music Network, 2021)
This collection delves yet deeper into the archives of country blues, uncovering hidden gems by artists shrouded in mystery, from classic renditions of blues standards to intriguing novelty songs.